Recent advances in ultra-small fluorescent Au nanoclusters toward oncological research - Yang, Jingjing; Wang, Fenglong; Yuan, Huiqing; Zhang, Lishu; Jiang, Yanyan; Zhang, Xue; Liu, Chao; Chai, Li; Li, Hui; Stenzel, Martina (Nanoscale, 2019)
Au nanoclusters possess a series of excellent properties owing to their size being comparable to the Fermi wavelength of electrons. For example, they show excellent biocompatibility, optical stability, large Stokes shift, intense size-dependent emission and monodispersion, and thus could effectively compensate for the shortcomings of traditional organic fluorescent dyes and fluorescent quantum. In this review, we detail the latest developments of Au nanoclusters employed in the field of biomedicine, especially in oncology research, by summarizing the application of imaging, sensing and drug delivery based on their excellent luminescent properties and unique structural features. We also discuss the significant work relating to Au NCs that now is being devoted in other therapeutic strategies, such as radiotherapy, photothermal therapy and photodynamic therapy, for example. It is anticipated that this review will provide new insights and theoretical guidance to allow the advantages of Au nanoclusters to be realized in oncotherapy. The structure, properties of gold nanoclusters and their applications in targeting anti-cancer fields have been reviewed.